Perbedaan Umur Panen terhadap Hasil dan Mutu Benih Tanaman Buncis (Phaseolus vulgaris L.) - SURYAWAN, KADE LICANA LARASATI; RAKA, I GUSTI NGURAH; MAYUN, IDA AYU; WIJAYA, I KETUT ARSA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.8, No.4, Oktober 2019, 2019)
Difference in Harvest Age Against the Results and Quality of Seedlings of Beans (Phaseolus vulgaris L.) This study aims to determine the effect of seed age on the yield and quality of beans. This research is a one factor research with three different age of harvest treatments are: harvest before physiological maturity 24 days after flower blooms, harvest at physiological maturity is 27 days after flower blooms, and harvest after physiological maturity is 30 days after flower bloom. This study used a randomized block design (RBD) with 9 replications. The observed variables included: the development of the seed wet weight, seed oven dry weight, seed moisture content, pod and seed character, percentage of good seed, weight of 1000 seed grains, seed germination, and seed growth simultaneity. The results showed that the pod harvest time for the best seeds was carried out at the age of 27 days after the flowers bloomed. At that time the highest dry weight of the seeds and pods had changed color from green to yellowish green. At that time the seeds also showed maximum quality characteristics, such as the percentage of good seeds (87.22%) and the weight of 1000 seeds (91.34 g). Physiological characteristics of seed quality such as seed germination capacity of 99.78% and 88.78% simultaneity of seed growth were also obtained at the time of pod harvest at 27 days after flower blooms.